The Implementation of Differentiated Instruction to Improve Students' Speaking Skills in an Academic Speaking Class - Ildi Kurniawan; Azhar Aziz Lubis; Eka Novita (Journal of English Language Studies, 2025)
This research aims to describe the extent to which the implementation of differentiated instruction (DI) can improve students' speaking skills in the academic speaking class and to describe students’ perception of the use of DI in the class. This is Classroom Action Research (CAR), which consists of two cycles (eight meetings), and each cycle covers the activity stages, including: plan, action, observation, and reflection. The subject of this research was students who took an academic speaking class at the English Department, University of Bengkulu, with 32 students in total. The data were collected qualitatively through observation and quantitatively through a speaking performance test and questionnaire. The collected data were then analyzed by using simple descriptive statistics. The results show that the implementation of differentiated instruction can help students' speaking skills. Also, almost all students show positive perception regarding the use of differentiated instructions in academic speaking. The students agree that the learning process using differentiated instruction provides them with interesting and encouraging activities, and the tasks given are based on students’ interest and their level of ability.